Justicia restaurativa: la desatinada prohibición de la mediación penal en los asuntos de violencia de género - Carlos Patricio, Serrano Lucero (2016)
Gender-based violence is a phenomenon that has gone from being ignored by the criminal law to becoming an excessive punitive burden today. This has led to, among other things, the prohibition of criminal mediation in matters of gender violence. The current criminal policy has not been as rates resulting gender violence have not decreased. In this contribution we will argue in favor of the implementation of criminal mediation in certain cases of gender violence, explaining the unfounded reasons for it being banned and advocating the benefits offered by this system of restorative justice